Perancangan Simulator Modulasi Analog dan Digital Berbasis App Designer Matlab untuk Media Pembelajaran Sistem Telekomunikasi - Naufal Arif Ardiansyah; Desi Fitriana; Shita Fitria Nurjihan; Fitri Elvira Ananda (Fakultas Teknik Universitas Muhammadiyah Parepare (FT-UMPAR), 2026)
This paper proposes an application that was designed using MATLAB App Designer in the form of an analog and digital modulation simulator that can be used as a learning tools in telecommunications systems courses. Studying the modulation process is one of the core areas of knowledge in the telecommunications field. Modulation is the process of superimposing an information signal on a carrier signal to produce a modulated signal. Modulation can be divided into analog modulation and digital modulation. Analog modulation is modulation with an input signal in the form of an analog signal, while digital modulation has an input signal in the form of a binary or digital signal. The results of designing analog and digital modulation simulators can display simulations of AM, FM, PM, ASK, FSK, and PSK modulation in the form of information signals, carrier signals, and modulation signals, as well as BER and SNR results for digital modulation. The simulator can work properly and in accordance with the theoretical analysis of analog and digital modulation. The greater the SNR level, the more the modulation system performance increases, because the BER (Bit Error Rate) value becomes lower.